Stable Weyl points, trivial surface states, and particle-hole compensation in WP2 - Razzoli, E.; Zwartsenberg, B.; Michiardi, M.; Boschini, Fabio; Day, R. P.; Elfimov, I. S.; Denlinger, J. D.; Suess, V.; Felser, Claudia; Damascelli, Andrea (Physical Review B, 2018)
A possible connection between extremely large magnetoresistance and the presence of Weyl points has garnered much attention in the study of topological semimetals. Exploration of these concepts in transition-metal diphosphides WP2 has been complicated by conflicting experimental reports. Here we combine angle-resolved photoemission spectroscopy (ARPES) and density functional theory (DFT) calculations to disentangle surface and bulk contributions to the ARPES intensity, the superposition of which has plagued the determination of the band structure in WP2. Our results show that while the hole- and electronlike Fermi surface sheets originating from surface states have different areas, the bulk-band structure of WP2 is electron-hole compensated in agreement with DFT. Furthermore, the ARPES band structure is compatible with the presence of at least four temperature-independent Weyl points, confirming the topological nature of WP2 and its stability against lattice distortions.
CRIS-Team Scopus Importer:2022-04-14